Cobalt and KNO3 supported on alumina catalysts for diesel soot combustion - Grzona, Claudia Beatriz (2010)
The catalytic combustion of diesel soot was studied in the presence of fresh and aged catalysts: Co/Al2O3, KNO3/Al2O3 and Co/KNO3/Al2O3. The catalysts were prepared by impregnation using nitrate solutions. The catalysts were characterized by X-ray diffraction, thermal programmed reduction, vibrational spectroscopy and X-ray photoelectron spectroscopy. Fresh and aged catalysts present high activity in presence of O2 and O2/NO. The values of the combustion temperature decrease more than 200 °C with respect to that observed in the process without catalysis. The activity is associated with the presence of KNO3 and the role of this salt can be attributed to the contribution of NO3−/NO2− redox cycle.